FROM MILLENNIALS TO 'SILVER ECONOMY': AN ANALYSIS OF TECHNOLOGY READINESS, USER EMANCIPATION, AND AI ADOPTION IN THE SOCIO-ECONOMIC TRANSFORMATION ECOSYSTEM - Asep; Aim Abdulkarim; Meila Yufriana Devi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The transition to cybernetic capitalism and the disruption of Artificial Intelligence (AI) have created a reality of